Vartotojų visuomenės užuomazgos Lietuvoje (XIX a. antra pusė–XX a. pradžia) - Ambrulevičiūtė, Aelita (Sociologija. Mintis ir veiksmas, 2013)
Santrauka. Šio straipsnio tikslas – nustatyti, kaip skirtingi Vilniaus, Kauno ir Gardino gubernijų visuomenės sluoksniai įsitraukė į masinį vartojimą XIX a. antrojoje pusėje–XX a. pradžioje. Šiame straipsnyje vadovaujamasi T. Vebleno parodomojo vartojimo samprata, pagal kurią prekėms suteikiama ne tik ekonominė, bet ir sociokultūrinė vertė. Straipsnyje analizuojami pasiturinčių (paprastai aukštesnių) visuomenės sluoksnių vartojimo įpročiai, kaip keitėsi žemesnių (paprastai mažiau pasiturinčių) visuomenės sluoksnių požiūris į vartojimą, kai atsirado fabrikinės gamybos, pirktinio daikto poreikis. Kreipiamas dėmesys į įsigyto daikto savininkui suteikiamą kultūrinę reikšmę, ar kokybiškai nauji daiktai leido keisti vartojimo įpročius ir pakilti į kokybiškai kitą vartojimo lygį. Pagrindiniai žodžiai: masinė gamyba, vartojimas, parodomasis vartojimas, vartotojiškoji visuomenė. Key words: mass-production, consumption, conspicuous consumption, consumption society. ABSTRACT ORIGIN OF CONSUMPTION SOCIETY IN THE LITHUANIA (SECOND HALF OF THE 19TH CENTURY–EARLY 20TH CENTURY) Prior to the spread of mass production goods, luxury products (which signified a high social status) were mostly made out of expensive materials and their costs were determined by the physical properties they had. Such goods were expensive in the truest sense of the word and they did not have any less expensive analogues, made out of cheaper materials. Everyday things of the upper class were usually out of reach for the lower social strata. That is why until the spread of goods of mass production, the difference between the goods used by the upper class and those used by the lower social strata emphasized various social group distinctions, and social status was recognized by socially corresponding products. Moreover, before the spread of goods of mass production, the lower social strata did not have an opportunity to take fashion tendencies into account and change their clothes, furniture and other household goods. They would use the things until they were completely worn out. Changing things according to the “fashion” as well as demonstrating a possibility of spending funds on luxury products was a common practice amongst the cultural elites. Slowly the attitude of the lower social strata towards consumption started to change, and a demand for manufactured, store-bought items began to rise. The purchasing and consumption habits of the less fortunate in the society began to be influenced not only by the functions or physical properties of the products, but also by the supposed social importance of the usage of them. Such products (in most cases this did not depend on its quality) were increasing the social rank of an individual in the society as well as emphasizing their lifestyle and wealth. Quite often the unique characteristics of a product and conveniences it provided in housekeeping, were less important than the cultural importance it provided to the owner. The ability to buy some housekeeping-related products provided greater comfort as well as new and good quality items, changed the consumption habits reaching a higher level. Expenditure on goods amongst the lower social strata acquired a representative social value and became means for demonstrating the financial standing and standard of living. Pastaba: straipsnis parengtas vykdant Lietuvos mokslo tarybos pagal Europos Sąjungos struktūrinių fondų remiamą projektą „Podoktorantūros (pos doc) stažuočių įgyvendinimas „Lietuvoje“.